Development of Educative Traditional Game Training Model Based on Local Potential in Improving the Knowledge and Skills of Early Childhood Parents - Wilda Putri Yeni (Universitas Negeri Padang, 2019)
The purpose of this study is to provide a training model that can improve the knowledge and skills of children's parents to carry out education in the family environment. To achieve this goal, traditional educational games are developed based on local potential. After attending the training, it is expected that the skills and knowledge of parents in implementing traditional games can be improved. This research method is a research and development model. The subjects of this study were parents of early childhoods who lived to look after their children during the study in Gorontalo City PAUD, 50 of which were used in previous studies and 40 others were used in the implementation model, and they were divided into two groups, groups experiment, and control (20 each). Purposive sampling, tests, interviews, questionnaires, and documentation studies were applied in this research. This implements quasi (Non-Pretivalent Group Pretest-Posttest Design) experiments. The results show that traditional educational models based on local potential have effectively improved the knowledge and skills of early childhood parents in PAUD.Keywords: Early Childhood Education, Traditional Games, Local Potential